2004
DOI: 10.1128/aac.48.8.3200-3202.2004
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Chlamydia trachomatis to Excipients Commonly Used in Topical Microbicide Formulations

Abstract: Commonly used "inactive" pharmaceutical excipients were tested in a previously developed minimum cidal concentration assay to assess their ability to kill Chlamydia trachomatis topically. Sixteen excipients were evaluated in these studies under various conditions. A range of activities was found among the excipients that could be tested in our assay system.Promising topical antimicrobial agents that are active against sexually transmitted infection pathogens have been identified (1, 10, 11), but these agents m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The buffered pH levels used in the current study were chosen to provide a point of comparison with the work of Lampe et al (8). While studies performed at pH 4 also demonstrated inhibition for serovar LGV/L2 (data not shown), the effect was less pronounced than that at pH 5 or 7.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The buffered pH levels used in the current study were chosen to provide a point of comparison with the work of Lampe et al (8). While studies performed at pH 4 also demonstrated inhibition for serovar LGV/L2 (data not shown), the effect was less pronounced than that at pH 5 or 7.…”
mentioning
confidence: 91%
“…Since new preventative antimicrobials could prevent chlamydial infection, there is much effort to develop microbicides and related compounds (7,20). Recently, a number of reports have highlighted the in vitro antichlamydial properties of polysaccharide-based chemotherapeutics and excipients (2,8,10,19). Studies on the basis of the antimicrobial properties of polysaccharides highlight the need for the use of excipient-only controls when the effectiveness of new antimicrobials is tested and contribute to our understanding of the molecular mechanism of chlamydial adhesion to polysaccharides or glycoproteins on the surface of host cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation